Innovation methodology for determination of particulate material in suspension and it’s application in the mining industry - Scandoleira, Fernando Cezar (2009)
The existents methodologies available for the proposal of determination of quantity of solids in the air, have low precision in the mining industry, this work presents an adaptation in a already and classic existent system, what transform it in a more precise one. This innovated methodology presents a big potential also in the fertilizer industry. The innovation of this equipment consists in a recipient with calculated dimensions that is used to “throw” the material that is going to be evaluated, causing the loose or a suspension of the dust; this material is collected through a system of filter, with a support and a special constant vacuum pump. This system is able to collect a representative quantity of particles separated, during a determinated period of time. After this, the system is weighted and the weigh is compared with the initial weigh, giving parameters for the definitions of the dust controls and treatments. It is a portable equipment, with good reproducibility and low cost, that takes in account the all the various and steps of an evaluation of the polluted atmosphere from solids particles. This paper was focused in a sector of the mining industry, the fertilizer sector, a very important economic area in Brazil. Using the proposed methodology, some different anti dusts were evaluated. The results of the evaluations done when compared between themselves, showed notables variations for some kind of anti dust when compared with the fertilizers without additives, then the precision of the new method can be considered good and it has a big potencial in the mining sector and in the fertilizer industry.